2007
DOI: 10.1152/physrev.00011.2006
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Arrhythmogenesis

Abstract: Triggered activity in cardiac muscle and intracellular Ca2+ have been linked in the past. However, today not only are there a number of cellular proteins that show clear Ca2+ dependence but also there are a number of arrhythmias whose mechanism appears to be linked to Ca2+-dependent processes. Thus we present a systematic review of the mechanisms of Ca2+ transport (forward excitation-contraction coupling) in the ventricular cell as well as what is known for other cardiac cell types. Second, we review the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
322
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(336 citation statements)
references
References 644 publications
(727 reference statements)
11
322
0
3
Order By: Relevance
“…We observed that AE do not propagate to the whole sarcolemma and thus cannot directly promote generalized cellular activity. On the other hand, spontaneous tubular activities can trigger local asynchronous SR Ca 2+ release, which contributes to nonuniform myofilament activation (29) and SR Ca 2+ content depletion (30), promoting contractile dysfunction in HF.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that AE do not propagate to the whole sarcolemma and thus cannot directly promote generalized cellular activity. On the other hand, spontaneous tubular activities can trigger local asynchronous SR Ca 2+ release, which contributes to nonuniform myofilament activation (29) and SR Ca 2+ content depletion (30), promoting contractile dysfunction in HF.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that DADs are mediated by Ca waves (47)(48)(49)(50), in which spontaneous SR Ca release from a group of adjacent CRUs recruits neighboring CRUs to initiate a propagating wave (51,52). On the other hand, the simulations in Fig.…”
Section: Mechanisms Of Dadsmentioning
confidence: 96%
“…So, with substantial increases of intracellular IP 3 concentrations as may occur following stimulation of cardiomyocytes with G q protein-coupled agonists, IP 3 Rs can become activated at normal diastolic Ca 2+ levels, or during the recovery of a stimulated Ca 2+ transient [62]. The promiscuous opening of IP 3 Rs during the otherwise quiescent diastolic period under these conditions is therefore the cause of arrhythmic Ca 2+ transients and their associated electrical activity [63,64].…”
Section: The Dilemma Of Cardiac Ip 3 Receptors: Lost In An Ocean Of Rmentioning
confidence: 99%